Educational Leadership and Organisational Culture: An Interdisciplinary Perspective - AL-HUSSAINI, SENABIL B. (2017)
This research explores the relationship between leadership and organisational culture in a sample of eleven schools based in the United Arab Emirates that are characterised by a hierarchical management structure. Following a mixed methods research methodology, the leadership styles of principals are classified as transformational, transactional or passive/avoidant. Then, through a qualitative grounded theory approach combined with symbolic interactionism the schools’ organisational culture is interpreted to reveal some of the hidden perspectives on schools’ leadership. The leadership images and pragmatics of language communicated by the participants are analysed in this research study for their associated complexities through the lens of speech act theory. An enhanced form of transforming leadership style was found to be predominant, encompassing a combination of transformational and transactional leadership. Seven theoretical categories of organisational culture were developed and examined in-depth in two selected schools, revealing that the leaders prefer to use redressive strategies in communicating face threatening acts; strategies indicating politeness and rational decision making. The style of leadership, which impacted on the schools’ organisational culture, was found to be strongly influenced by practices from a higher level of schools’ administration and management. School leaders’ polite communication style served as a partial shielding effect to some of the external influences, and the attitudes of individual principals and their styles of leadership were enacted in varied ways. In conclusion, this research proposes a three-dimensional model to interpret organisational culture and leadership influence on organisations such as schools which are embedded in multi-level hierarchical management structures.